Investigating relationship between religious commitment and moral sensitivity in nurses working in ICU - Khalighi, Ebrahim (BMC Res Notes, 2020)
OBJECTIVES: This study aimed at determining the relationship between religious commitment and moral sensitivity among nurses working in the ICU sections in the west of Iran. The present study was a cross-sectional descriptive-analytic study carried out on nurses working in ICU wards of two western cities in Iran. The instrument used includes a demographic questionnaire, religious commitment questionnaire and moral sensitivity questionnaire in nurses. First, the researchers referred to the ICU wards of the hospitals in the cities after receiving permission from the relevant authorities by referring to three shifts in the morning, evening and night shifts and holidays. The researchers, while explaining the research goals for the nurses participating in the study, obtained their informed consent to participate in this study. RESULTS: According to the findings, mean (SD) of the overall score of religious commitment was equal to 36.38 (4.58) and mean (SD) of MS score of nurses was 59.21 (12.65). Also, 91 nurses (82.7%) had average MS, 7 (6.4%) had low MS and 12 (10.9%) had high MS.